2013
DOI: 10.1017/s1460396913000216
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying daily variation in volume and dose to the prostate, rectum and bladder using cone-beam computerised tomography

Abstract: Introduction: In the era of dose escalation for localised prostate cancer, the dose-volume histogram (DVH) is integral to the assessment of rectum and bladder dose constraints. However, reliance on a single planning computerised tomography-based (P-CT) dose distribution may not account for variations in delivered dose that results from deformation of the prostate, bladder and rectum. This study uses conebeam CT (CBCT) datasets from five patients to investigate the concordance between the dose prediction from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…However, variations in the daily setup and physiological changes in the volumes of the bladder and rectum can result in displacement and deformation of the prostate during treatment, consequently changing the dose distribution to the target and adjacent organs (3) . Dosimetric studies have indicated that the DVH produced at the time of planning may not be an exact representation of the actual dose received during treatment (4) . Translational shifts in the prostate during the course of radiotherapy have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, variations in the daily setup and physiological changes in the volumes of the bladder and rectum can result in displacement and deformation of the prostate during treatment, consequently changing the dose distribution to the target and adjacent organs (3) . Dosimetric studies have indicated that the DVH produced at the time of planning may not be an exact representation of the actual dose received during treatment (4) . Translational shifts in the prostate during the course of radiotherapy have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the magnitude of dose differences to a target strongly depends on the patient. Another study by McParland et al 29 that evaluated fractional doses to prostate cancers showed that the dose differences to the prostate CTV D 98% decreased by 3% for the mean and 4.6% for the maximum. This inconsistency is attributed to the differences in the total treatment period, beam energy, and image quality of CBCT.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings are difficult to compare to the literature, where studies in conventional prostate radiotherapy describe varying methods to assess delivered dose with only two studies identified in the SABR setting. 15,18,[24][25][26][27][28][29][30][31][32] Evidence of volume changes is lacking in SABR with inter fraction rectal variation well documented in conventional radiotherapy. 17,25,26,33,34 We found no systematic change for rectal volume, although Maund et al (2014) report rectal volume decreases on treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Dose-volume histogram (DVH) data are derived from CT, which forecasts treatment dose, meaning effects of daily organ changes may be ignored. [14][15][16][17] For this reason, DVH being representative of the delivered plan is central to the success of an advanced planning technique. 18 Organ motion can result in setup error and geometric uncertainty, which may negatively impact target coverage and normal tissue dose.…”
mentioning
confidence: 99%